Kırsal Alanlarda Yaşayan Yerel Halkın Kişilik Tipleri ve Turizm Algısı - Ayaz, Nurettin; Parlak, Uğur (Journal of History Culture and Art Research, 2019)
Local People Personality Types and Perception of Tourism in Rural Areas Abstract Tourism is one of the important dynamic sectors that play a role in the development of the regions. However, attractiveness, accessibility, tourism operations and support of local people are essential for the development and sustainability tourism in a region. The aim of this study is to reveal the residents’ perceptions towards tourism according to their personality in Ardahan and to contribute to the development of tourism in the region. In order to reach research purposes, the data was collected from 400 locals living in Ardahan using a questionnaire and the convenience sampling method was concluded that local people’s personality types can be categorized in five dimensions as; extrovert, being prone to use, cold and lack of self-confidence. Besides, residents’ perception towards tourism can be examined in three dimensions as positive impacts of tourism and negative social and environmental impacts of tourism. The results show that local people give importance positive impacts of tourism as well as negative environmental and social impacts. Moreover, in conclusion, extraverted locals are keen to support tourism. Kırsal Alanlarda Yaşayan Yerel Halkın Kişilik Tipleri ve Turizm Algısı Öz Turizm, bölgelerin kalkınmasında rol üstlenen önemli dinamik sektörlerden birisidir. Bununla birlikte bir bölgede turizmin gelişebilmesi ve devamlılığı için çekicilik, ulaşılabilirlik, turizm işletmeleri gibi turistik arz kaynakları ve yerel halkın desteği gerekmektedir. Bu araştırmada Ardahan ilinde yaşayan yerel halkın kişilik tiplerine göre turizm algısının ortaya çıkarılması ve ilde turizm gelişimine katkı sağlanması amaçlanmaktadır. Bu amaç doğrultusunda Ardahan ilinde yaşamakta olan yerel halktan anket tekniği kapsamında tesadüfi örneklem yöntemi kullanılarak 400 anket toplanmıştır. Araştırmada yerel halkın kişilik tipleri; dışa dönük, kullanılmaya yatkın, baskın, soğuk ve kendine güvensiz olmak üzere beş boyutta şekillenmiştir. Yerel halkın turizm algısı ise turizmin olumlu etkileri ile olumsuz çevresel ve olumsuz toplumsal etkileri olmak üzere üç boyutta incelenmiştir. Araştırma sonucunda yerel halkın turizmin olumlu etkilerinin yanı sıra olumsuz çevresel ve toplumsal etkilerini de önemsedikleri görülmüştür. Ayrıca dışa dönük kişiliğe sahip toplum üyeleri turizmi daha çok kabul etmeye ve desteklemeye hazırdırlar.